TINDAK PIDANA PENODAAN BENDERA MERAH PUTIH BERDASARKAN UNDANG-UNDANG NOMOR 24 TAHUN 2009 TENTANG BENDERA, BAHASA, DAN LAMBANG NEGARA SERTA LAGU KEBANGSAAN DIKAITKAN DENGAN ASAS PERSAMAAN DI HADAPAN HUKUM - Rizky Soehantoro; Erdianto Effendi; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Since the 1945 Constitution applies, Indonesia as a rule of law gives a message of a strong desire that the state guarantees the equality before the law. In the 1945 Constitution there is also the red and white flag which is the flag of the Indonesian state. The red and white flag as an identity and identity of the Indonesian state. In its use the red and white flag cannot be arbitrary, therefore, this red and white flag becomes sacred. Although the arrangement was made in Law No. 24 of 2009 concerning Language Flags and State Symbols and National Anthems, however, there is no equal treatment before the law against the crime of desecration of the red and white flag. Due to the absence of separation of acts it is prohibited to make anyone processed until the court and some are not processed until the court. The purpose of writing this thesis are: First, to find out the law enforcement against the crime of desecration of the red and white flag based on Law Number 24 of 2009 concerning Flags, Languages and State Emblems and National Anthems in Indonesia. Secondly, to find out the limits of tainting the criminal act of desecration of the red and white flag based on Law Number 24 of 2009 concerning Flags, Languages and State Symbols and the National Anthem. Third, to find out the ideal arrangement for the crime of desecration of the Red and White Flag based on Law Number 24 of 2009 concerning Flags, Languages, and State Symbols and the National Anthem is associated with the principle of equality before the law. This type of research is normative legal research. From the results of the research problem there are three main points concluded, first, law enforcement against crimes of desecration of the red and white flag in Indonesia is still relatively weak, because the regulation in Article 66 and Article 24 letter a as a related article, does not separate acts prohibited from making law enforcement there those who are legally processed until a court and some are not processed by law until the court. So that causes unequal treatment before the law. Secondly, the limitation of desecration in the crime of desecration of the red and white flag is not so clear that the act of being an abstract makes the one related to the red and white flag so it can be categorized as a crime of desecration of the red and white flag. Third, Article 66 and Article 24 letter a as related articles of Law No. 24 of 2009 concerning National Flags, Languages and Symbols, and the National Anthem currently available is not yet effective enough. Due to the absence of separation of acts which were prohibited in the criminal act of desecration of the red and white flag. The absence of an ideal arrangement and not yet listed or not yet reflected in the principle of equality before the law in the regulation so as to make law enforcement difficult. Keywords: Crimes-desecration-White-Red Flag-Principle of equality before the law